2017
DOI: 10.2147/ijn.s124584
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of antagomiR204-conjugated gold nanoparticles from PLGA sheets and its implication in promoting osseointegration of titanium implant in type 2 diabetes mellitus

Abstract: Impaired osseointegration of the implant remains the big hurdle for dental implant therapy in diabetic patients. In this study, the authors first identified that miR204 was strikingly highly expressed in the bone mesenchymal stem cells (BMSCs) of diabetic rats. Forced expression of miR204 repressed the osteogenic potential of BMSCs, while inhibition of miR204 significantly increased the osteogenic capacity. Moreover, the miR204 inhibitor was conjugated with gold nanoparticles (AuNP-antagomiR204) and dispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
(40 reference statements)
0
32
0
Order By: Relevance
“…In vitro delivery of anti-miR-155 with PMO and PNA modification demonstrated significant knockdown of miR-115 [ 221 ] whereas, in vivo study further demonstrated that PLGA nanoparticles encapsulating anti-miR-155 PNA could accumulate in the pre-B cell tumours through enhanced permeability and retention effect [ 222 ]. On other hand, Liu et al demonstrated that anti-miR-204 encapsulated with PLGA nanoparticles promotes osteogenesis in type 2 diabetes [ 223 ]. To date only limited reports available for using nanoparticle-mediated delivery of miRs to treat cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro delivery of anti-miR-155 with PMO and PNA modification demonstrated significant knockdown of miR-115 [ 221 ] whereas, in vivo study further demonstrated that PLGA nanoparticles encapsulating anti-miR-155 PNA could accumulate in the pre-B cell tumours through enhanced permeability and retention effect [ 222 ]. On other hand, Liu et al demonstrated that anti-miR-204 encapsulated with PLGA nanoparticles promotes osteogenesis in type 2 diabetes [ 223 ]. To date only limited reports available for using nanoparticle-mediated delivery of miRs to treat cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of tissue necrotic factor (TNF) and reduction in bone morphogenetic protein-6 (BMP-6) are some of the reported mechanisms that could be implicated for delayed or failed osseointegration in diabetic cases [45,46]. Coating of polylactic-co-glycolic acid (PGLA) containing miR204 inhibitors and gold nanoparticles on the implant to overcome such attenuation has been reported to enhance implant homing [47]. However, the current study implies that the localized administration of inductive BMMSCs from a healthy rabbit can enhance osseointegration in diabetic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from DM have increased the frequency of tooth loss due to periodontitis, impaired response to infection, and delayed wound healing.Successful osseointegration of the dental implant in DM patients is a challenge and matter research since long. 1,2 Al Zahrani and Al Mutairi 1,3 evaluated stability and peri-implant bone loss (PIBL) around non-submerged and submerged dental implants in patients with and without T2DM. Increased PIBL was found around non-submerged implant-supported restorations in T2DM patients.…”
mentioning
confidence: 99%
“…In the case of T2DM patients, for early intervention of postextraction, alveolar ridge preservation surgery is recommended. 9 Liu et al 2 found that miR204 misexpression accounted for the deficient osseointegration in DM. In T2DM patients, better osseointegration can be obtained by poly (lactic-co-glycolic acid) (PLGA) sheets which aid in the release of gold nanoparticles (AuNP-antagomiR204), and helps in the functionalization of the titanium implant surface and overcome the poor bone-implant contact in T2DM.…”
mentioning
confidence: 99%
See 1 more Smart Citation